Genetic Analysis of Yield Contributing Traits in Lowland Rice Genotypes under Acidic Soils - Debnath, Ashim; Rai, Mayank; Tyagi, Wricha; Das, Sudip (International Journal of Bio-resource and Stress Management, 2017)
Five cultivars adapted to the lowland acidic soils of the North Eastern Hill Region were crossed with three elite varieties that are not grown in the region, in a line×tester design, in order to study their combining ability with respect to yield contributing traits under acidic lowland soils of Meghalaya. The performance of parents was also evaluated under aluminium toxic hydroponics conditions. Genetic analysis revealed locally adapted cultivars Priya and Sahbhagi Dhan to be the best general combiners, while among the testers, IR 24 and Kasalath showed the best general combining ability (GCA). Individual crosses Sahbhagi Dhan×Kasalath, Shahsarang×Samba Mahsuri SUB1, Priya×IR 24 showed the best specific combining ability (SCA). The most prominent specific cross was Sahbhagi Dhan×Kasalath, which showed the highest heterotic value when compared against the best commercial cultivar of the region (Shahsarang) with respect to majority of the traits studied. The GCA of the tester Kasalath was highest for all the traits, whereas line Sahbhagi Dhan showed highest GCA for biological yield, grain yield and harvest index. The study suggests that segregating populations of cross Sahbhagi Dhan×Kasalath would be ideal for selection of high yielding transgressive segregants adapted to acidic soils. Hydroponic screening under aluminium toxic condition revealed BoroDhan and Shasarang to be the most tolerant parents as they accumulated high root and shoot biomass. These lines can be used as donors in breeding programmes aimed at enhancing tolerance to aluminium toxicity under acidic soils.